If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -1y = -15 Combine like terms: -4y + -1y = -5y -5y = -15 Solving -5y = -15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-5'. y = 3 Simplifying y = 3
| n-1.5=5.1 | | 12/18=8/y | | 6-(-1+8i)-(-7-i)= | | (10x-5y)=1 | | 2-6(r-6)=2+6(r-2) | | 4a-7=-59 | | 85+5x+10=180 | | 14=3v+5(v-2) | | 4a-7=59 | | b=1.5mv | | 9-8q+4q= | | 2q+1q= | | 75=6x+5x+9 | | 52+2x-6=180 | | -5-2n=21 | | 3(5n)+14+6n=21 | | -2(3x+6)=12 | | x(x+5)=210 | | 2X^2+-8X=0 | | 5(r-2)=-16+6r | | (-2x+4)-(-6x-7)= | | 3x-45=2y | | -6(2x-1)=0 | | x^2-15=-7x+2 | | 23-5n=-7(n-3)-4 | | 0.1x+0.2y=-0.2 | | Log^4*16=2 | | 7x-(5x+4)=9x-25 | | 25=2u+3u | | 2(x+4)4=0 | | 7.4x-13.4=31 | | 8u-u=21 |